A ORDEM DO DISCURSO NA EDUCAÇÃO ESPECIAL - Alcântara, Ramon Luis de Santana (2011)
My main objective in this research is, taking the Foucault´s idea of speech and the scheme knowledge-truth-power to analysis the approaches and aloofnesses between the speech about teacher formation in Special Education in São Luís and the speech in the official documents about this subject. To reach this objective it is used some concepts of Michel Foucault: speech, speech formation, device, event, subject, subjectification, knowledge, truth, power, strategy, conflict, tactics, identity, governmentality, biopower, biopolitics, State, Education. My theoretical methodological reference works taking the central positional that is attributed to the speech. The objective is to analysis the speeches taking the Foucault s concepts that are evidenced in the speech. The methodological procedures to this paper as a researcher are cartographies, (taking Gilles Deleuze and Felix Guattari), semi structured interviews, questionnaires, and the documental analysis. In this theoretical methodological reference the research subjects are a possibility of speech. The subject is a shape, a part of the speech. Taking this idea the sources to this research are regular teacher in the city of São Luís and the official documents about teacher formation and Special Education in São Luís and Brazil. It was taken 20 teachers in São Luís and many official devices between 1988 and 2009. As a result it is designed a Brazilian neoliberal governmentally that directs the educational politics. Also, it is presented the formation politics that conform a teacher identity, as a technology of State. Another result is the set of problematizations established by the political and scientific field to create a new teacher, the inclusive teacher, a new teacher to the Inclusive Education. About the teacher speeches and official devices it was observed the maintenance of the idea relating difference to deficiency that takes the inclusive politics only as a possibility to access and permanence and ignores the problematization about difference. The speech about Special Education in São Luís is formed taking power relations and objectives comprehend the impasse between notion of difference and inclusive speech formation and the possibilities to include taking this perspective.